VERGEVING: VERKENNINGEN RONDOM EEN DELICAAT THEMA - W. Wessels (Acta Theologica)
Peels, H.G.L. (ed.), (APELDOORNE STUDIES NR 76, 2020), 125 pp. Price: € 15,95 (paperback), ISBN: 978-90-75847-53-6. bestellen@tua.nl